Assessing factors that influence perceived burnout in postdoctoral fellows and identifying recommendations to support their well-being - Suzanne C. Harris; Emma Smits; Robert McGinity; Jacqueline M. Zeeman (PLoS ONE, 2026)
Background While current evidence suggests rates of stress and burnout among healthcare professionals and graduate trainees are up to 50%, higher than the general population, there is a critical gap in the literature concerning factors which influence well-being among postdoctoral fellows in health sciences programs. This exploratory study aims to identify factors influencing well-being and burnout among these postdoctoral fellows and identify recommendations to improve their well-being. Methods A two-stage sampling approach was used: (1) Purposive sample of postdoctoral fellows employed at a public university were recruited to participate in semi-structured focus groups to assess workplace factors which influence their perceived burnout and well-being and to solicit recommendations to improve well-being; (2) Stratified sampling was used to assign participants into focus groups by industry-sponsored or academic (non-industry-sponsored) positions to explore experiences that may be unique to these groups. Inductive coding and thematic analysis of Zoom transcripts were used. Results Seven postdoctoral fellows participated in three focus group sessions, with two industry-sponsored fellows in one group, three academic fellows in one group, and two academic fellows in one group. Participants identified insufficient resources, difficult transition, and workload and program structure as factors contributing to their perceived burnout. Factors contributing to their well-being included reasonable supervisor expectations, personal and professional support, and resource support. Participant recommendations to improve well-being included institutional initiatives and resources, additional non-supervisor support, and workload strategies. Conclusions This study expands upon the sparse literature on postdoctoral fellows by exploring factors that contribute to their perceived well-being and burnout, as well as provide suggestions to support their well-being. Findings contribute to the broader conversation of postdoctoral fellow well-being and burnout and informs the academy of focused strategies to improve their well-being and reduce burnout.